PRODUKTIVITAS PERTANIAN DAN PENDAPATAN PETANI: BUKTI DARI INDONESIA - Nurulia Dimitha (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2026)
Agricultural productivity is widely recognized as a critical driver of rural welfare and poverty reduction in developing economies; however, empirical evidence on how productivity gains translate into farmers’ income remains fragmented, particularly in the context of heterogeneous smallholder systems. This study investigates the productivity–income nexus in Indonesian agriculture by providing integrated empirical evidence on the extent to which productivity improvements, technological adoption, and institutional support shape farmers’ income outcomes. Employing a mixed-methods approach, this study combines quantitative analysis of farm-level survey data across major agricultural regions with qualitative insights from farmer interviews to capture both measurable outcomes and contextual dynamics. The results reveal a strong and statistically significant positive relationship between agricultural productivity and farmers’ income, with technology adoption emerging as a key transmission mechanism through which productivity gains are converted into higher income levels. However, the magnitude of income gains varies substantially across regions and farm characteristics, reflecting disparities in access to extension services, markets, and institutional support. The study’s novelty lies in demonstrating that productivity growth alone is insufficient to ensure inclusive income improvements unless supported by effective extension systems and enabling institutional environments. By explicitly linking productivity performance with income distribution among smallholder farmers, this research contributes to the agricultural economics and development literature and offers policy-relevant insights for designing productivity-enhancing interventions that generate sustainable and equitable income growth in Indonesia.